1989
DOI: 10.1007/bf00683121
|View full text |Cite
|
Sign up to set email alerts
|

Levels of benzene and other volatile aromatic compounds in the blood of non-smokers and smokers

Abstract: The concentrations of benzene, toluene, ethylbenzene, and o-, m-and p-xylene were measured in venous blood samples collected from 13 non-smokers and 14 cigarette smokers. The blood samples were analysed by a purge and trap technique followed by gas chromatography/mass spectrometry/computer analysis. The above-mentioned volatile organic compounds (VOC) could be detected in measurable amounts in all blood samples. This finding seems to reflect the ubiquitous exposure of humans to these agents in the urban enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…For example, Brugnone et al (11) reported that in Italy the mean blood benzene level of smokers (381 ppt) was significantly higher than that of nonsmokers (205 ppt); both of those levels are about 2 times or more higher than the mean blood benzene level reported herein. We also found lower benzene blood levels than those reported in Germany by Hajimiragha et al (12) and Angerer et al (13). Our mean benzene level is similar to that reported by Jermann et al (14) for a population living in a European city with high traffic density.…”
Section: Results Vocssupporting
confidence: 89%
“…For example, Brugnone et al (11) reported that in Italy the mean blood benzene level of smokers (381 ppt) was significantly higher than that of nonsmokers (205 ppt); both of those levels are about 2 times or more higher than the mean blood benzene level reported herein. We also found lower benzene blood levels than those reported in Germany by Hajimiragha et al (12) and Angerer et al (13). Our mean benzene level is similar to that reported by Jermann et al (14) for a population living in a European city with high traffic density.…”
Section: Results Vocssupporting
confidence: 89%
“…1-1, and the values agreed with our measurements from nonsmoking persons. The maximal benzene level in the blood of unexposed nonsmokers reported in the literature is about 6 nmol· 1-1, and that of unexposed smokers about 12-15 nmol · I-I (15,16). When nonsmoking subjects were exposed to a benzene concentration of 1.7 crrr' .…”
Section: Discussionmentioning
confidence: 93%
“…From published data ( Wallace et al, 1987;Hajimiragha et al, 1989 ) it may be concluded that the ratio of ethylbenzene to the other C8 -aromatics is somewhat higher in cigarette smoke than in auto exhaust. Again, stepwise regression analysis was applied to identify the main sources of exposure.…”
Section: Sources Of Exposure To C8 -Aromaticsmentioning
confidence: 99%